ERS/EACTS statement on the management of malignant pleural effusions. Issue 1 (27th July 2018) - Bibby, Anna C.; Dorn, Patrick; Psallidas, Ioannis; Porcel, Jose M.; Janssen, Julius; Froudarakis, Marios; Subotic, Dragan; Astoul, Phillippe; Licht, Peter; Schmid, Ralph; Scherpereel, Arnaud; Rahman, Najib M.; et al.
Malignant pleural effusions (MPE) are a common pathology, treated by respiratory physicians and thoracic surgeons alike. In recent years, several well-designed randomised clinical trials have been published that have changed the landscape of MPE management. The European Respiratory Society (ERS) and the European Association for Cardio-Thoracic Surgery (EACTS) established a multidisciplinary collaboration of clinicians with expertise in the management of MPE with the aim of producing a comprehensive review of the scientific literature. Six areas of interest were identified, including the optimum management of symptomatic MPE, management of trapped lung in MPE, management of loculated MPE, prognostic factors in MPE, whether there is a role for oncological therapies prior to intervention for MPE and whether a histological diagnosis is always required in MPE. The literature revealed that talc pleurodesis and indwelling pleural catheters effectively manage the symptoms of MPE. There was limited evidence regarding the management of trapped lung or loculated MPE. The LENT score was identified as a validated tool for predicting survival in MPE, with Brims' prognostic score demonstrating utility in mesothelioma prognostication. There was no evidence to support the use of oncological therapies as an alternative to MPE drainage, and the literature supported the use of tissue biopsy as the gold standard for diagnosis and treatment planning. Management options for malignant pleural effusions have advanced over the past decade, with high-quality randomised trial evidence informing practice in many areas. However, uncertainties remain and further research is required http://ow.ly/rNt730jOxOS